2011
DOI: 10.1111/j.1365-2303.2011.00943.x
|View full text |Cite
|
Sign up to set email alerts
|

Borderline nuclear change, high‐grade dyskaryosis not excluded: current concepts and impact on clinical practice

Abstract: The B/HG category was associated with a significantly higher incidence of CIN2+ compared with borderline cytology as a whole. This refining performance justifies its existence. Colposcopic appearances had a high PPV for detecting CIN2+. Therefore, colposcopy is recommended in patients with B/HG cytology and treatment should be offered if high-grade colposcopic changes are seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Because HPV testing has a known (albeit low) false‐negative rate, 23 a negative hrHPV test result in the presence of ASC‐H cytology does not guarantee the absence of high‐grade CIN and such women may require careful follow‐up rather than routine recall. Irrespective of hrHPV status, a second issue relates to the relatively high positive predictive value of ASC‐H for CIN2 or worse lesions, averaging at around 40% 24–26 . Given these data, it may be unwise to disregard ASC‐H cytology in women with negative colposcopic findings, as not all high‐grade lesions are visible at colposcopy 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Because HPV testing has a known (albeit low) false‐negative rate, 23 a negative hrHPV test result in the presence of ASC‐H cytology does not guarantee the absence of high‐grade CIN and such women may require careful follow‐up rather than routine recall. Irrespective of hrHPV status, a second issue relates to the relatively high positive predictive value of ASC‐H for CIN2 or worse lesions, averaging at around 40% 24–26 . Given these data, it may be unwise to disregard ASC‐H cytology in women with negative colposcopic findings, as not all high‐grade lesions are visible at colposcopy 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The ALTS study demonstrated the value of subcategorizing ASC‐US and ASC‐H with 41% of ASC‐H cases having underlying high‐grade intraepithelial lesion (HSIL) as compared to 12% in ASC‐US cases 3. Other studies have also confirmed the significance of subtyping ASC cases into ASC‐H 4–9. The majority of the previous studies are on conventional cervical smears.…”
mentioning
confidence: 85%